Consumers’ attitude towards date marking system of packaged foods - Mirghotbi, Mostafa; Pourvali, Katayoun (Archives of Advances in Biosciences, 2013)
Food labels play an important role in well being of consumers. As a part of it, date marking is a valid guide to shelf life of a food. The present study was done in 2010, in Smart Food Center, Wollongong; New South Wales, Australia to determine if the residents are familiar with date marking of food products. Data was accumulated by either interview guide or questionnaire method. Basic unselected samples of 200 shoppers were interviewed. Awareness of consumers about the method of date marking of food products, the frequency of purchasing spoiled or stale products, particularity about dates marked on food products before buying them, observation of the date marked on perishable and semi perishable food items, and satisfaction of consumers with the freshness and date marking of products were mainly studied. Out of 200 consumers who were interviewed, 112 (56%) supported date marking services. 128 (64%) consumers were well informed of the date making system. Most of the people in this group were between 35 to 44 years of age. 75% were or respondents women. The range of family income was between AUS30000-750000 per months. There was no association between degree of knowledge of date marking and sex and educational level of consumers who purchased spoiled food products. Among consumers who purchased spoiled food items, a significant number were informed of date marking systems and used it when making purchases. Date marking has been observed by both male and female and was not related to their academic degrees.